Challenges of contemporary policing : higher education, technology, and officers' well-being - Riccio, Vicente; Jia, Di; Das, Dilip K., 1941- (Routledge, 2025)
"This edited collection reflects contemporary challenges faced by police forces across the globe and the role of technology in addressing them. The use of science and technology raises questions about ethics, training, the well-being of people, and freedom. New technologies promise to foster police practices based on intelligence, accuracy, and preparedness, and are considered necessary to overcome challenges such as declining budgets, lack of personnel, and legitimacy. However, technologies can also be used for authoritarian and nefarious purposes. For those reasons, this book aims to discuss related topics from various contexts to establish connections among common problems in the field of policing across the globe. This book provides an internationally relevant assessment of the use of technology in the field of policing, as well as the impact on training and police well-being. It is ideal for an academic audience at both graduate and undergraduate levels in the fields of criminal justice studies, police studies, environmental criminology, legal sociology, and public policy, and will be of interest to police practitioners, legal professionals, social service workers, and public-sector managers"-- Provided by publisher.
Keywords: Police administration.; Justice, Administration of.; Management -- Technological innovations.; elektronické knihy; electronic books